Development of audit assignment tracking system prototype - Thanasegaran Subrayan (2021)
The aim of this research is to find a solution in assisting a private Bank’s Information Technology Audit Unit which is facing issue with current arrangement of work from home, as there is no automated system/too; to assist them in their daily task. The Banks policy on restricting the movement of confidential file and data have also restrict the task that the auditors can perform remotely. The objective of this project is to assist or mitigate the issue faced while working from home by developing a working prototype of an audit management system. The methodology used in building the audit assignment tracking System which is a Prototype methodology will assist in understanding the needs of the audit team involved as the user will be involve actively in all the stages. The proposed system will resolve most of the issues faced by the Information audit team as the manual workflow will be transformed to automated process workflow. (Abstract by author)